2021
DOI: 10.1016/j.medj.2020.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Primary Human Colonic Mucosal Barrier Crosstalk with Super Oxygen-Sensitive Faecalibacterium prausnitzii in Continuous Culture

Abstract: Many human gut bacteria of clinical relevance are extremely oxygen sensitive, hampering the investigation of crosstalk with host cells. Zhang et al. developed a gut-microbe physiomimetic platform for long-term continuous co-culture of super oxygen-sensitive bacterial species with primary human colon epithelium in the context of inflammation.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
91
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(93 citation statements)
references
References 118 publications
(139 reference statements)
2
91
0
Order By: Relevance
“…Through a radial oxygen gradient generated by the system, intestinal cells were oxygenated whereas anaerobic conditions allowed microbiota growth, as assessed by real-time monitoring via integrated noninvasive oxygen sensors [19,36]. Similar physiological hypoxia conditions were achieved by Zhang and coworkers who cocultured oxygen super-sensitive bacterial species using a differently designed MPS, the GuMi (Figure 3C) [37]. This platform induced a steep oxygen gradient through the addition of a long-term continuous flow of anoxic apical medium and aerobic basal media.…”
Section: Trends In Biotechnologymentioning
confidence: 70%
See 1 more Smart Citation
“…Through a radial oxygen gradient generated by the system, intestinal cells were oxygenated whereas anaerobic conditions allowed microbiota growth, as assessed by real-time monitoring via integrated noninvasive oxygen sensors [19,36]. Similar physiological hypoxia conditions were achieved by Zhang and coworkers who cocultured oxygen super-sensitive bacterial species using a differently designed MPS, the GuMi (Figure 3C) [37]. This platform induced a steep oxygen gradient through the addition of a long-term continuous flow of anoxic apical medium and aerobic basal media.…”
Section: Trends In Biotechnologymentioning
confidence: 70%
“…(C) Schematic representation of the GuMi physiome platform. Intestinal epithelial cells are cocultured in standardized Transwell® with anaerobic bacteria by using apical anoxic media and basolateral aerobic media applied to the system with individual flow control (image adapted, with permission, from [37]). (D) A Transwell® format MPS configuration allows the integration of up to 10 organ tissues (image reproduced, with permission, from [50]).…”
Section: En Route To Replicating the Gut-kidney Axis Using Mpssmentioning
confidence: 99%
“…In another study, Zhang et al developed a Gut-Microbiome physiome platform featuring primary human colon epithelial cells and oxygen-sensitive commensal anaerobe ( Faecalibacterium prausnizii ) to investigate mucosal barrier-bacterial interactions. Under flow condition, it has been demonstrated that F. parausnizzi exerted anti-inflammatory effects through the production of butyrate and subsequently downregulated toll-like receptor (TLR)-3 and TLR-4, responsible for activation of nuclear factor-light-chain-enhancer of activated B cells (NF-KB) signaling and inflammation [ 226 ]. In another organ-on-a-chip model featuring liver (human hepatocytes and Kupfer cells) and gut (ulcerative colitis epithelium, dendritic cells, and macrophages), Trapecar et al showed the involvement of effector CD4 T cells in modulating cellular metabolism and inflammatory response [ 227 ].…”
Section: Organ-on-a-chip Platforms For Assessment Of Nanoparticle Toxmentioning
confidence: 99%
“…For example, the native intestine is more complex than the simple epithelium. Incorporation of components of the normal host microenvironment such as endothelial, immune, and neuronal cells and the microbiome, which can result in enhanced or reduced replication of different infecting microbes, will validate whether these cultures can fully recapitulate human mucosal tissues where most infections begin [62,[95][96][97][98]. While it is unclear whether genetically matched tissue (mesenchyme, immune, and neuronal cells and the HIO) will be required to establish such cultures, human organoid cocultures offer the first controllable system to understand the mechanisms of immune or neuronal cells or microbial interactions and competition leading to enhanced or inhibitory outcomes.…”
Section: Summary and Current Questionsmentioning
confidence: 99%